2014
DOI: 10.1177/0956462414556328
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcome of first-line antiretroviral therapy among HIV-1 vertically-infected children in Hanoi, Vietnam

Abstract: A retrospective analysis of 86 HIV-1 vertically-infected Vietnamese children with a follow-up period >24 months after initiating antiretroviral therapy (ART) was performed from 2008 to 2012, to assess the outcome of first-line ART in resource-limited settings. Of the 86 children, 68 (79.1%) were treated successfully (plasma HIV-1 viral load [VL] <1000 copies/ml), and 63 (73.3%) had full viral suppression (VL <400 copies/ml) after 24 months of ART. No significant difference between successfully treated patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The total study population was 86, with 68 children having VL <1000 copies/ml and 64 having full viral suppression with VL <400 copies/ml after 24 months of ART. There was no significant difference between successfully treated patients and failure groups in terms of clinical parameters and demographics at the baseline [22]. Among the children with treatment failure, one developed reverse-transcriptase inhibitor resistance mutations by 24 months of treatment.…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 77%
See 2 more Smart Citations
“…The total study population was 86, with 68 children having VL <1000 copies/ml and 64 having full viral suppression with VL <400 copies/ml after 24 months of ART. There was no significant difference between successfully treated patients and failure groups in terms of clinical parameters and demographics at the baseline [22]. Among the children with treatment failure, one developed reverse-transcriptase inhibitor resistance mutations by 24 months of treatment.…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 77%
“…None of the successfully treated patient developed DRMs. The most dominant NNTRIs and NRTIs resistance mutations were Y181C and M184V/I, respectively [22].…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2008, we have followed up with HIV-infected children in Hanoi, Vietnam to find an efficient and cost-effective method and immunological markers for monitoring ART in resource-limited settings [18]. Based on the results of that field study, we conducted this cross-sectional study to clarify the impact of HIV infection and ART on the immune profile and microbial translocation status of children aged over 2 years who have an immune status considered to be relatively mature and stable [9,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As well as the increased immune system disturbance compared with adults, the rate of treatment failure in HIV‐infected children is also much higher than that in adults. Pham et al . reported that the treatment failure rate in HIV‐infected children on anti‐retroviral therapy (ART) in Vietnam was 25% after a 36 month follow up.…”
mentioning
confidence: 99%